The role of physical activity in the occurrence of depression, anxiety, and stress levels among high school students: A correlational study - Yusfi, Herri; Fitri, Arfa Desa; Bayu, Wahyu Indra; Destriana; Solahuddin, Soleh (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
The COVID-19 pandemic has had a significant impact on physical activity levels, particularly in the context of physical education, leading to a decline in students' physical fitness. This decline in physical fitness may have implications for students, potentially increasing their vulnerability to stress, depression, and anxiety. Therefore, this study aimed to examine the relationship between physical activity and levels of anxiety, stress, and depression among students during the COVID-19 lockdown period. A descriptive quantitative research design was employed, utilizing a correlational method to explore the associations between physical activity and mental health outcomes. The International Physical Activity Questionnaire (IPAQ) and the Depression Anxiety Stress Scale (DASS 42) were used as research instruments. The study included students from Lubuk Linggau 3 State High School, with a sample size of 166 students selected through accidental sampling. Data analysis involved the implementation of Chi-squared and MANOVA tests using Excel and SPSS 25 software. Surprisingly, the study findings revealed no significant relationships between physical activity and depression, anxiety, or stress levels among the participants. Therefore, it can be concluded that physical activity alone may not directly cause depression, anxiety, and stress among students at Lubuk Linggau 3 State High School during the COVID-19 lockdown period. To enhance the generalizability of these findings, future studies should include a more diverse range of participants, such as students from urban areas. Furthermore, exploring additional factors that may contribute to mental health outcomes during the pandemic can provide a more comprehensive understanding of the complex interplay between physical activity and psychological well-being. By expanding the scope of research, valuable insights can be gained to develop tailored interventions and support systems aimed at promoting the overall mental well-being of students across diverse educational contexts.